AKSI SOSIAL PENGEMBANGAN DESA WISATA DI KABUPATEN BREBES UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT - Rahmawati Zulfiningrum (Program Studi Akuntansi IKOPIN, 2021)
Social action has the orientation of a fundamental change in the structure ofsociety. The process and results are the orientation of social action, through aprocess of increasing awareness, community empowerment, and real communityactions organized so that they can make changes to the power structure to realizethe principles of justice, democracy, and equality. Based on the observation datain the field, there are quite a several schools that are close to potential tourismobjects. This condition triggers the emergence of social action in the context ofdeveloping tourist villages to preserve the existing potential as well as improve thecommunity's economy. This research uses interview, observation, and literaturereview methods. The results of the analysis show that identification efforts in thedevelopment of tourist villages in Brebes District are needed to improve thecommunity's economy as one of the mainstays of tourism, especially increasingsupporting facilities and infrastructure as operational technical completeness. It isintended that tourist villages in Brebes District can have high competitiveness, byapplying the concept of participatory sustainable tourism and paying attention toindigeneous knowledge, social capital, and local wisdom.